Transient and Steady Pervaporation of 1-Butanol-Water Mixtures through a Poly[1-(Trimethylsilyl)-1-Propyne] (PTMSP) Membrane - Talluri, Vssl Prasad; Patakova, Petra; Moucha, Tomas; Vopicka, Ondrej (Polymers, 2019)
The transient and steady pervaporation of 1-butanol-water mixtures through a poly[1-(trimethylsilyl)-1-propyne] (PTMSP) membrane was studied to observe and elucidate the diffusion phenomena in this high-performing organophilic glassy polymer. Pervaporation was studied in a continuous sequence of experiments under conditions appropriate for the separation of bio-butanol from fermentation broths: feed concentrations of 1.5, 3.0 and 4.5 w/w % of 1-butanol in nutrient-containing (yeast extract) water, temperatures of 37, 50 and 63 °C, and a time period of 80 days. In addition, concentration polarization was assessed. As expected, the total flux and individual component permeabilities declined discernibly over the study period, while the separation factor (average β = 82) and selectivity towards 1-butanol (average α = 2.6) remained practically independent of the process conditions tested. Based on measurements of pervaporation transients, for which a new apparatus and model were developed, we found that the diffusivity of 1-butanol in PTMSP decreased over time due to aging and was comparable to that observed using microgravimetry in pure vapor in 1-butanol. Hence, despite the gradual loss of free volume of the aging polymer, the PTMSP membrane showed high and practically independent selectivity towards 1-butanol. Additionally, a new technique for the measurement and evaluation of pervaporation transients using Fourier transform infrared spectroscopy (FTIR) analysis of permeate was proposed and validated.
Keywords: pervaporation; water; PTMSP; butanol; ageing; diffusivity